Energy harvesting system using reverse electrodialysis with nanoporous polycarbonate track‐etch membranes. (21st September 2013) - Kwon, Kilsung; Lee, Seung Jun; Li, Longnan; Han, Changheon; Kim, Daejoong; Ali, N.; Lund, P.
SUMMARY Energy harvesting technology has recently gained attraction as it enables the utilization of diverse ambient energy sources. Reverse electrodialysis (RED) is such a technique that converts electrical energy from the concentration gradient between a concentrated solution (e.g., seawater) and a diluted solution (e.g., fresh water). We experimentally investigated a RED device using nanoporous polycarbonate track‐etch membranes. We performed the parametric study by varying the concentration differences, the pore size, and the electrolyte types. We characterized the RED performance in terms of maximum voltage, maximum current, and maximum power. The experimental results showed that the maximum voltage has a nonlinear dependency on the concentration difference with the highest value around the 100:1 concentration ratio. The maximum current and maximum power, on the other hand, monotonically increase as the concentration difference increases. We also found that the performance of the RED cell is enhanced with the decreased pore size in the experiments for the nominal diameter ranging from 15 to 100 nm. The results with different cations show that the electricity generation of the RED cell increases as the ion mobility increases or the valence number decreases. Copyright © 2013 John Wiley & Sons, Ltd.